If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + -4w = -5w + -7 Reorder the terms: -2 + -4w = -7 + -5w Solving -2 + -4w = -7 + -5w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '5w' to each side of the equation. -2 + -4w + 5w = -7 + -5w + 5w Combine like terms: -4w + 5w = 1w -2 + 1w = -7 + -5w + 5w Combine like terms: -5w + 5w = 0 -2 + 1w = -7 + 0 -2 + 1w = -7 Add '2' to each side of the equation. -2 + 2 + 1w = -7 + 2 Combine like terms: -2 + 2 = 0 0 + 1w = -7 + 2 1w = -7 + 2 Combine like terms: -7 + 2 = -5 1w = -5 Divide each side by '1'. w = -5 Simplifying w = -5
| (2x-9)-(3x-3)=-(3x+3)-3x+9 | | 3=p*15 | | 6x+12y+15z= | | 11x+2=8x | | -9p=-10-10p | | t^2+16t+60= | | -3x=4y+8 | | 3(4g+6)=2+(6g+9) | | 10+n=-n | | 8-5(z-2)=-2(5z-2)-2 | | -6j+6=-8j | | 10x-8y=26 | | 10x+5=3+4x-8 | | -4+3f=2f | | 6(6x+1)=9(4x-3)+5 | | -7+6(-8n+8)=(-2+5)+7 | | C+2c+c=20 | | 7+19t-2=9t+107-7t | | x+(3)=-7 | | 5x*2-1+2x*2+x+5=0 | | 3(-3y-3)=-9+23 | | 20c-15c=10 | | 11=7x+1-5x | | 110-4x=170-8x | | -5a-4a+2a=14 | | -22=4x-6x-2 | | 2.7+10m=6.35 | | 9-2x=3(2x-5) | | 3(x-5)+2=7(2-x)+1 | | 4r+16=4r-32 | | 6-x-1=6-[x+1] | | 10+6y-6y=7 |